Cerebral palsy specific growth charts for Indian children: need of the hour - Choudhary, Govind; Inamdar, Nusrat Rahim; Mauskar, Anupama (International Journal of Contemporary Pediatrics, 2022)
Background: Children with cerebral palsy (CP) are generally undernourished and growth retarded. The nutritional assessment and anthropometry have important role in management of these problems. Reference growth curves for Indian children with CP may be helpful to clinicians and beneficial to children for better assessment of nutritional status and to monitor growth. This study was conducted to compare the anthropometric inferences derived from specific growth curves for CP developed by centers for disease control (CDC) with that of using WHO and IAP growth curves. Methods: Cross sectional observational study conducted on 40 children with CP aged 2 to 12 year. Through universal sampling. Anthropometric variables measured and plotted on age and gender specific growth curves for cerebral palsy and on WHO / IAP growth curves. Nutritional assessments on these growth curves are then compared. Results: Number of underweight children were more on WHO/IAP growth curves 52.5% (n=21) compared to CP specific growth curves 20% (n=8) (p=0.002) similarly, number of stunted children were more on WHO/IAP growth curves (40% versus 0%) compared to CP specific growth curves (p=0.0001) both being statistically significant. No significant difference was seen on comparing BMI (p=0.067). Conclusions: Significant difference in nutritional status is observed when anthropometric variables are compared on two curves (CP specific versus WHO/IAP curves). Applying WHO/IAP growth curves, to assess the growth of children with cerebral palsy may not be appropriate and may have fallacies with interpretations of growth and nutritional status. Apart from nutrition, functional status and co morbidities also play a vital role in deciding nutritional status. Disease specific or standardized growth charts for Indian children with CP may play an important role in early diagnosis and management of growth faltering.